TEACHER EXPERIENCES IN A COLLABORATIVE ARTS PROJECT BETWEEN SCHOOLS AND ARTS COMMUNITIES IN LEARNING SEGO MEGONO DANCE AT STATE MIDDLE SCHOOL 12 PEKALONGAN - Fonny Arista; M. Jazuli (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The development of digital technology has affected various areas of life, including art education and art learning in schools, now faced with the demands for significant change. Learning dance arts in schools has an important role in developing students' creativity, expression, and understanding of cultural values and students get deep and meaningful experiences. This study aims to describe and analyze the didactic and aesthetic experiences of teachers as well as the implications of collaborative art projects between schools and communities in the learning of Sego Megono Dance at SMP Negeri 12 Pekalongan.  The method of this study is qualitative with an autoethnographic study approach. Autoethnography is a research method that combines an autobiographical approach with ethnography, in this case the researcher reflects on personal experiences in the social and cultural context of the local culinary Sego Megono which is interpreted through dance, to understand a phenomenon more deeply. The research procedure has several stages, namely the preparation stage, the research implementation stage, the data collection stage, the data analysis stage and the reporting stage. The results of the study show that the collaborative art project between schools and the art community in learning Sego Megono Dance reveals the didactic and aesthetic experiences of students, teachers and the art community in learning Sego Megono Dance at SMP Negeri 12 Pekalongan. This teacher's experience obtained new findings, namely students' interest in learning dance art increased, students became more interested and active and gained aesthetic experience from the dance art community and dance teachers. Teachers gain learning innovations, collaborative strategies and pedagogic reinforcement. The implications of collaborative art projects show that collaboration-based art learning can be a bridge between education and community culture. The collaboration not only strengthens the quality of art learning in schools, but also assists ARH Dance Management as an art community in introducing and promoting Sego Megono Dance through formal school education.